Ciguatoxin â€“ an Emerging Biological Hazard among Reef Fishes of India - Rajisha, R.; Kishore, Pankaj; Panda, S. K.; Ashok Kumar, K. (Fishery Technology, 2018)
Ciguatera Fish Poisoning (CFP) is an emerging food safety hazard which has been reported in southern peninsular India in recent times. Ciguateric fishes mostly associated with coral reef ecosystem are implicated in food poisoning outbreaks. USFDA guidance for fish and fishery products classifies CFP as â€œreasonably likely to occurâ€ in fishes harvested from coral reef regions. Ciguatera Fish Poisoning has been reported from tropical or subtropical areas around the world between latitudes 35Â°N and 35Â°S, particularly in the Caribbean, Pacific and Indian Ocean and in the Flower Garden Banks area in the northern Gulf of Mexico. Action levels for CFP limits are now listed as 0.01 ppb for Pacific and 0.1 ppb for Caribbean ciguatoxin. CFP is considered as a natural toxin and USFDA has listed out 12 group of fishes under ciguatera hazard category. With recent EU import rejections of some of the seafood consignments originated from India, CFP has emerged as an important food safety concern. Although, no fatality has been reported so far, morbidity symptoms observed from cases of hospitalization is a definite concern to the export trade. This review deliberates on the significance of CFP, its distribution and hazard control measures.